Gigaspora roseae and Coriolopsis rigida Fungi Improve Performance of Quillaja saponaria Plants Grown in Sandy Substrate with Added Sewage Sludge - Guillermo Pereira; Diyanira Castillo-Novales; Cristian Salazar; Cristian Atala; Cesar Arriagada-Escamilla (Journal of Fungi)
The use of living organisms to treat human by-products, such as residual sludge, has gained interest in the last years. Fungi have been used for bioremediation and improving plant performance in contaminated soils. We investigated the impact of the mycorrhizal fungus (MF) Gigaspora roseae and the saprophytic fungus (SF) Coriolopsis rigida on the survival and growth of Quillaja saponaria seedlings cultivated in a sandy substrate supplemented with residual sludge. Q. saponaria is a sclerophyllous tree endemic to Chile, known for its high content of saponins. We inoculated plants with the MF, the SF, and a combination of both (MF + SF). Following inoculation, varying doses of liquid residual sludge equivalent to 0, 75, and 100% of the substrate’s field capacity were applied. After 11 months, we found a positive influence of the utilized microorganisms on the growth of Q. saponaria. Particularly, inoculation with the SF resulted in higher plant growth, mycorrhizal colonization percentage, and higher enzymatic activity, especially after the application of the sludge. This increase was more evident with higher doses of the applied sludge. These results highlight the potential of combined microorganism and residual sludge application as a sustainable strategy for enhancing plant growth and reducing waste.